THE INFLUENCE OF MINDFUL THOUGHT ON EMOTIONAL REGULATION IN ADULTS: A LITERATURE REVIEW - Haryati Septiani; Meidiana Dwidiyanti; Megah Andriany (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: Mental disorder is one of the most difficult problems to overcome in the world and one of the causes is about the low emotional regulation. Emotional regulation is influenced by a person's awareness in managing his emotions. For increasing the emotional regulation need some interventions to enhance mindful thought and the benefits will appear. Objectives: This article aimed to explain the benefits of mindful thought in emotion regulation and the type of intervention can be used to improve mindful thought in adults. Design: This study used a scoping review to review the articles the influence of mindful thought on emotional regulation in adults. Data Sources: Data based used were Science Direct, Scopus, SpingerLink, PubMed and Emerald Insight from 2017 to 2021. The literature obtained by using the Booleon operators “OR/AND” search. The keywords in the search were